2014
DOI: 10.4038/suslj.v12i1.6990
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and participation of farmers in extension activities of agricultural media resources and extension centre in Ogun state

Abstract: This study assessed the extension activities of Agricultural Media Resources and Extension Centre (AMREC) of University of Agriculture Abeokuta, Ogun State. Five villages that were in active collaboration with the centre were targeted. Ten percent (10%) of registered farmers were selected from each village given the sample size of 170 respondents. Data based on respondents awareness and participation in the extension activities of AMREC were collected through structured questionnaire and analysis was done usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…This result suggests that once the farmers are aware of the extension activities, a large proportion of them are likely to participate in these activities. As mentioned earlier, this result is supported by Fawole and Tijani (2013) …”
Section: Resultssupporting
confidence: 77%
“…This result suggests that once the farmers are aware of the extension activities, a large proportion of them are likely to participate in these activities. As mentioned earlier, this result is supported by Fawole and Tijani (2013) …”
Section: Resultssupporting
confidence: 77%
“…Current findings confirmed by Ajadi et al (2016), revealed that farmers who had contact with extension department were aware. These finding are also supported by Fawole & Tijani (2013) which showed high correlation between participation of farmers in extension activities and their awareness. According to (Umeh et al (2018), extension improved farmers' decision power, analytical abilities by communicating sound suggestions and information.…”
Section: Discussionsupporting
confidence: 63%
“…Okwu & Daudu, (2011) reported that in Benue state of Nigeria, interpersonal communication channels such as extension agents, contact farmers, opinion leaders and friends/ neighbours were generally preferred by the farmers to the mass media to obtain information on improved farm technologies. Several studies including (Daudu, Chado & Igbashal, 2009;Fawole & Tijani, 2013;Ogunremi, Faturoti & Oladele, 2011;Kwarteng, & Okorley 2014) have revealed that the village level extension agent is the most effective source of information for farmers but certainly not the most efficient in terms of cost and coverage. Afful & Lategan, (2014) reported that in Free State province, South Africa, public extension was the dominant information source for production activities for most farmers.…”
Section: Introductionmentioning
confidence: 99%